Microbial community succession in the intestine of mice with deep partial-thickness burns - Chen, Li-Jian; Liu, Yi; Yang, Jing-Wen; Lin, Yan; Hsu, Clare; Zhang, Kai-Kai; Liu, Jia-Li; Li, Jia-Hao; Li, Xiu-Wen; Yang, Jian-Zheng; Chen, Long; Zeng, Jia-Hao; et al. (Frontiers in Microbiology, 2023)
Introduction: Burn injury has been shown to lead to changes in the composition of the gut microbiome and cause other damage in patients. However, little is known about how the gut microbial community evolves in individuals who have recovered from burn injury. Methods: In this study, we established a model of deep partial-thickness burn in mice and collected fecal samples at eight time points (pre-burn, 1 day, 3 days, 5 days, 7 days, 14 days, 21 days, 28 days post-burn) for 16S rRNA amplification and high-throughput sequencing. Results: The results of the sequencing were analyzed using measures of alpha diversity, and beta diversity and taxonomy. We observed that the richness of the gut microbiome declined from day 7 post-burn and that the principal component and microbial community structure varied over time. On day 28 after the burn, the microbiome composition largely returned to the pre-burn level, although day 5 was a turning point for change. Some probiotics, such as the Lachnospiraceae_NK4A136_group, decreased in composition after the burn but were restored in the later recovery period. In contrast, Proteobacteria showed an opposite trend, which is known to include potential pathogenic bacteria. Conclusion: These findings demonstrate gut microbial dysbiosis after burn injury and provide new insights into the burn-related dysbiosis of the gut microbiome and strategies for improving the treatment of burn injury from the perspective of the microbiota.